Analisis Pengaruh Kualitas Website terhadap Kepuasan Pengguna Website UPI Kampus di Purwakarta (Current Research in Education: Conference Series Journal, 2023)
UPI Campus in Purwakarta has an information system in the form of a website that is useful as a means of information for the public outside and within the university. The UPI Campus website in Purwakarta is a web-based information service that was built and developed by the website developer at UPI Purwakarta. The website portal kd-purwakarta.upi.edu is the official website of the UPI campus in Purwakarta, where all information is available on the website. The existence of information services is not yet known, so the measurement of user satisfaction with the system needs to be measured. This study aims to produce a design assessment of the influence of website quality on user satisfaction. The method used is the Webqual 4.0 method, with as many as 22 question attributes and analyzed using the Importance Performance Analysis (IPA) method. The results of the study obtained a design assessment of the influence of website quality based on indicators that are influenced by the quality of use, quality of information, quality of interaction and user satisfaction. The conclusion is that the analysis of the influence of website quality on user satisfaction can be done using the Webqual 4.0 and IPA methods.